2020
DOI: 10.1016/j.artd.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Taper fretting corrosion with Stryker Anato stem after hip replacement

Abstract: We report a case of head-neck taper fretting corrosion in a patient who had a total hip replacement with a noncemented Stryker Anato femoral stem and a V40 metal head with a Stryker Tritanium hemispherical socket with a highly cross-linked polyethylene liner (metal on polyethylene) (Stryker, Mahwah, NJ, USA). A 57-year-old man presented with early-onset hip pain after right total hip arthroplasty. Workup was negative for infection. Metal artifact reduction sequence MRI revealed an encapsulated fluid mass. Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Furthermore, the femoral head scores were positively correlated to implantation time ( r 1/4 0.35, P < 0.05) . In another example of a head/neck taper fretting, a metal artifact sequence from a 57-year-old with a noncemented Stryker Anato femoral stem and V40 with Stryker Titanium indicated an encapsulated fluid mass and cobalt ion level of 6 ppb . It has been reported that once the fretting process starts, it may continue without loading, with some retrieved tapers indicating signs of etching and grain egression typical of fatigue from macroscopic movements …”
Section: Corrosion In Arthroplastymentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the femoral head scores were positively correlated to implantation time ( r 1/4 0.35, P < 0.05) . In another example of a head/neck taper fretting, a metal artifact sequence from a 57-year-old with a noncemented Stryker Anato femoral stem and V40 with Stryker Titanium indicated an encapsulated fluid mass and cobalt ion level of 6 ppb . It has been reported that once the fretting process starts, it may continue without loading, with some retrieved tapers indicating signs of etching and grain egression typical of fatigue from macroscopic movements …”
Section: Corrosion In Arthroplastymentioning
confidence: 97%
“…(3) Last, metal oxides and insoluble metal hydroxides (rust products) form deposits on the surface of the metal . Thus, the chemistry of corrosion as an electrochemical phenomenon on arthroplastic implants is complex and usually starts on a spot, in which oxidation converts the space into an anodic region. , Electrons released at the anode move through the metal and reduce oxygen, in the presence of hydrogen ions (cathode), thereby producing oxides or salts of the original metals.…”
Section: Corrosion In Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation